If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3x+10=2(x+3)
We move all terms to the left:
3x+10-(2(x+3))=0
We calculate terms in parentheses: -(2(x+3)), so:We get rid of parentheses
2(x+3)
We multiply parentheses
2x+6
Back to the equation:
-(2x+6)
3x-2x-6+10=0
We add all the numbers together, and all the variables
x+4=0
We move all terms containing x to the left, all other terms to the right
x=-4
| 5.36=5.2+x | | 11x-1=-287 | | |(2x−5)/2|=1 | | -5y+1=-8+6y | | 7^-4x=17^x-7 | | 3(5c-5)=-30 | | X-3+2x=3 | | 3(u+3)-6u=-6 | | (D3+6D2+11D+6)y=0 | | -7w+2=-9(w-2) | | 6x-3(x+6)=4x-1 | | 4k=2k-12. | | r+2=-5 | | 10x+-2x=100 | | v-7=-1 | | 2=-8+k | | 2=p+10 | | 8x-6=5x-45 | | -1=r-6 | | -4=-7+m | | 24-16=2(x-1) | | -7+m=-4 | | 5x-5=9x-2 | | 2-2n-2n=5n-3n | | -2u+4(u+4)=20 | | 4•x+8=36 | | -1=2y+3(y-7) | | -7=-5+k | | 1.2(t-2)-6.2(t+6)=-5.3 | | `1.2(t-2)-6.2(t+6)=-5.3 | | 8y-12=4y-20 | | x/5+1.2=11.3 |